Menentukan Kelipatan Persekutuan Terkecil (KPK) dan Faktor Persekutuan Terbesar (FPB) dengan Menggunakan Metode PEBI - Suci Yuniati (Universitas Islam Negeri (UIN) Mataram, 2012)
Mathematics is a tool to develop ways of thinking, because mathematics is indispensable for both daily life and progressing science and technology so that mathematics needs to be taught to each student since elementary school, even since kindergarten. Establishing a thorough understanding of math requires a priorly love of math. Therefore a teacher should be able to create